Fresh food sustainable distribution: cost, delivery time and carbon footprint three-objective optimization. (April 2016) - Bortolini, Marco; Faccio, Maurizio; Ferrari, Emilio; Gamberi, Mauro; Pilati, Francesco
Abstract: This paper presents a three-objective distribution planner to tackle the tactical optimization of fresh food distribution networks considering operating cost, carbon footprint and delivery time goals. The developed expert system overcomes the widely adopted methodologies mainly focused on the cost minimization only. These three independent goals are jointly included in a unique tool, called Food Distribution Planner, to support the tactical planning of multi-modal distribution networks of perishable produces. This expert system implements a three-objective linear programming model, considering the typical food distribution constraints, i.e. the food quality dependence on the delivery time, the geographically distributed market demand and the farmer production capacities. This paper further applies the proposed system to a real case study dealing with the distribution of fresh fruits and vegetables from a set of Italian producers to several European retailers. The most effective distribution network is studied best balancing the economic, environmental and delivery time objective functions. Such a tactical network planning leads to 9.6% CO2 emission reduction with 2.7% cost increase compared to the correspondent single-objective configurations. Finally, the delivery time allows no produce waste due to the food quality preservation during shipment. Highlights: Cost, emissions and time multi-objective optimization for fresh food distribution. Multi-produce, multi-modal, multi-level distribution network planning. Food perishability during transport evaluated through the quality loss function. Case study of Italian consortium to distribute fresh produces to European retailers. Cost, carbon footprint and delivery time Pareto frontier determination & evaluation.